Respuesta :
Answer:
Step-by-step explanation:
(-b±√b²-4ac)/2a
(4±√-4²-4(2)(3))/2(2)
(4±√16-24)/4
(4±√8)/4
=4+√8 ║4-√8
-------- --------
4 4
idont know kung tama ba ito
or
(2x-3) (x-1)=0
2x-3=0 x-1=0
2x=3 x=1
x=3/2 x=1
We have that Solution to the quadratic equation 2x² - 4x + 3 = 0 is
Root [tex]x= 1 + 0.707i[/tex]
Root [tex]y= 1 - 0.707i[/tex]
From the question we are told that
2x² - 4x + 3 = 0
Generally the equation for solving Quadratic equation is is mathematically given as
([tex](x,y)=\pm b\frac{\sqrt{}b^2-4ac}{2a}\\\\(x,y)=\pm b\frac{\sqrt{(-4)^2-4*2*3}}{2*2}[/tex]
From the Deductions
Root x= 1 + 0.707i
Root y= 1 - 0.707i
Therefore
Solution to the quadratic equation 2x² - 4x + 3 = 0 is
Root [tex]x= 1 + 0.707i[/tex]
Root [tex]y= 1 - 0.707i[/tex]
For more information on this visit
https://brainly.com/question/23366835?referrer=searchResults